2019
DOI: 10.28991/cej-2019-03091360
|View full text |Cite
|
Sign up to set email alerts
|

Design Changes in Construction Projects – Causes and Impact on the Cost

Abstract: Isolation of design phase from construction has made the design changes inevitable in construction projects. Extensive literature appraisal has acknowledged the detrimental effect of design changes on project performances. However, the impact and causes of design changes have been divided up, either separately or project specific. As a result, the relationship between impact and causes of design changes could not be established for general construction. The primary objective of this paper is to examine the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 30 publications
1
26
0
2
Order By: Relevance
“…Additionally, a correlation was established to understand the relationship between the causes of change for each category. Aslam et al [13] identified the impact of design change on cost while also pinpointing actions that are responsible for these changes. They indicated that 45.85% and 27.1% of the causes of design changes are related to the designer and contractor, respectively.…”
Section: Causes Of Design Changementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a correlation was established to understand the relationship between the causes of change for each category. Aslam et al [13] identified the impact of design change on cost while also pinpointing actions that are responsible for these changes. They indicated that 45.85% and 27.1% of the causes of design changes are related to the designer and contractor, respectively.…”
Section: Causes Of Design Changementioning
confidence: 99%
“…Previous studies have covered much ground when it comes to design change. Researchers have focused on important topics on design change such as its causes [8,9], its impacts [5,10,11], its effects on cost [12,13], its impact on schedules [14], the parties responsible for design change, its root causes, its management and other impact aspects that contribute significantly to the body of knowledge on the subject. However, the majority of previous studies on design change have focused on residential and commercial building projects and civil areas.…”
Section: Introductionmentioning
confidence: 99%
“…Akibat dari terhentinya pekerjaan menimbulkan jadwal penyelesaian proyek yang terlambat dan kenaikan biaya (Yap et al, 2016) Perubahan design merupakan risiko yang memiliki dampak yang tinggi terhadap keterlambatan proyek risiko. Ini bisa terjadi karena adanya permintaan owner maupun permintaan buyer pada owner (Kristiana, 2017) Kurangnya komunikasi diantara stakeholder menjadi salah satu penyebab utama adanya perubahan design, padahal perubahan design ini dapat menyebabkan perbedaan biaya pada range 5%-40% (Aslam et al, 2019) Perubahan design pada proyek konstruksi selalu tidak dapat dihindarkan dan menyebabkan gangguan pada performance proyek.Owner menjadi penyebab utama sebagai pihak yang mempengaruhi perubahan design (Yana et al, 2015) Terjadinya keterlambatan proyek di Surabaya diakibatkan perubahan design oleh pemilik serta kekeliruan design oleh konsultan perencana (Bruno, 2019) Perubahan design oleh owner pada proyek jalan raya di Manado menjadi salah satu penyebab keterlambatan proyek. Pentingnya komunikasi yang baik antara kontraktor, konsultan dan owner supaya proyek berjalan dengan baik (Palulun et al, 2017) Perubahan design pada design struktur atap pembangunan gedung kantor DPRD Riau menimbulkan dampak keterlambatan waktu dan peningkatan biaya sebesar 29% (Sandyavitri, 2008.…”
Section: Pendahuluanunclassified
“…Management risk namely, poor, or improper planning and communication, external and internal collaboration, design errors and ineffective teamwork [16][17][18][19][20]. Technical risk namely, lack of training, low wages, inadequate safety measures in the execution, physical obstructions, frequent changes in the design, poor quality of materials [21][22][23][24]. Legal and political assessment comprising, errors in the contract documents, legal terms and procedural landscape, improper documentation, lack of records, loss of revenue by the state, undefined bureaucracy and corruption in the construction sector [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%